Comparative Cell Biology and Evolution of Annexins in Diplomonads - Elin Einarsson; Ásgeir Ástvaldsson; Kjell Hultenby; Jan O. Andersson; Staffan G. Svärd; Jon Jerlström-Hultqvist (mSphere, 2016)
ABSTRACT Annexins are multifunctional, calcium-binding proteins found in organisms across all kingdoms. Most studies of annexins from single-celled eukaryotes have focused on the alpha-giardins, proteins assigned to the group E annexins, expressed by the diplomonad Giardia intestinalis. We have characterized the annexin gene family in another diplomonad parasite, Spironucleus salmonicida, by phylogenetic and experimental approaches. We constructed a comprehensive phylogeny of the diplomonad group E annexins and found that they are abundant across the group with frequent gene duplications and losses. The annexins of S. salmonicida were found to be related to alpha-giardins but with better-preserved type II Ca2+ coordination sites. Two annexins were confirmed to bind phospholipids in a Ca2+-dependent fashion but with different specificities. Superresolution and confocal microscopy of epitope-tagged S. salmonicida annexins revealed localization to distinct parts of the cytoskeleton and membrane. The ultrastructural details of the localization of several annexins were determined by proximity labeling and transmission electron microscopy. Two annexins localize to a novel cytoskeletal structure in the anterior of the cell. Our results show that the annexin gene family is expanded in diplomonads and that these group E annexins are associated mostly with cytoskeletal and membrane structures. IMPORTANCE Annexins are proteins that associate with phospholipids in a Ca2+-dependent fashion. These proteins have been intensely studied in animals and plants because of their importance in diverse cellular processes, yet very little is known about annexins in single-celled eukaryotes, which represent the largest diversity of organisms. The human intestinal parasite Giardia intestinalis is known to have more annexins than humans, and they contribute to its pathogenic potential. In this study, we investigated the annexin complement in the salmon pathogen Spironucleus salmonicida, a relative of G. intestinalis. We found that S. salmonicida has a large repertoire of annexins and that the gene family has expanded separately across diplomonads, with members showing sequence diversity similar to that seen across kingdom-level groups such as plants and animals. S. salmonicida annexins are prominent components of the cytoskeleton and membrane. Two annexins are associated with a previously unrecognized structure in the anterior of the cell.